HUBUNGAN ANTARAMOTIVASI KERJADENGAN EFEKTIFITAS KERJAPENGAWAS SEKOLAH DI KOTA PEKANBARU - Itja, Desti (Jurnal Ilmu Administrasi Negara, 2008)
The problem that will be discussed in this research is whether or not there is a relationshipbetween work motivation and effectiveness of work supervision in Pekanbaru. The objective of theresearch is to analyze the relationship between work motivation and effectiveness of work supervisionin Pekanbaru. The research concludes that there is a positive correlation between; and workmotivation (X) and effectiveness of work supervision (Y). This research uses survey with proportionaltechnique. The population of this research is school supervisors in Pekanbaru. The sample ofthe research is 40 of the population selected by using simple random sampling. The instrument ofreseach use the modification of Gutman scale mode questioner to take the data about work motivationand effectiveness of work supervision. This study used simple correlation, partial correlation,and double correlation technique in analyzing the data. The result of analyzing data concludes that(1) there is positive correlation between work motivation and effectiveness of school work supervisionwhere regression standard ? =57, 58+ 0.48X1correlation coefficient r u = 0.52 and significant level a= 0.0 1.